Increasing PV penetration level in low voltage distribution system using optimal installation and operation of battery energy storage. Issue 1 (1st January 2019) - Khaboot, Nathphol; Chatthaworn, Rongrit; Siritaratiwat, Apirat; Surawanitkun, Chayada; Khunkitti, Pirat
Abstract: Photovoltaic (PV) systems are one of the most popular technologies to produce electricity from renewable energy, which can efficiently accommodate electricity demand. However, there are some issues occurring at high PV penetration levels in the distribution system. In order to increase the PV penetration level, battery energy storage system (BESS) has been widely integrated with PV systems because it could overcome issues during high PV penetration level and greatly provide optimal energy management. Then, this paper aims to increase the PV penetration level in low voltage (LV) distribution system by installation of BESS. The 41-bus practical radial LV distribution system located in Ratchaburi province, Thailand was focused. The net present value (NPV) was used as an economic indicator indicating the profitability of installing BESS. The optimal sitting, sizing, and operation of BESS yielding the maximum total NPV were determined. Then, the maximum PV penetration level was predicted for 10 case studies. In addition, the method for flattening load profile was appropriately adapted to be used in the LV distribution system. The genetic algorithm (GA) was performed to solve the optimization problem. The results showed that total NPV was increased with increasing the PV penetration level. The PV penetration level of 130% was found to be a suitable value for this particular system, which could provide significant improvement in NPV compared to the conventional system. The optimal BESS sizing and siting including the optimal BESS operation were also demonstrated.